Fenomenul ocupării în România şi dezvoltarea durabilă - Preoteasa, Ana Maria (Calitatea Vieții, 2008)
This article presents the employment situation in accordance with the sustainable development strategy and is focused on employment problems, as well as on employment policies. Concept of employment is defined using objective indicators (employment rate, unemployment rate, sectors of economy) and subjective: (working conditions evaluation, possibility to find a job, satisfaction with job and profession), and the results show a visible growth in employment in Romania, in the last years. Empirical analysis is based on statistical and survey data. The employment policy analysis took into consideration the EU employment strategy "more and better jobs": salary policies, unemployment policies and jobs quality policies. Two principles are important in the modern employment policy philosophy: flexibility and security of jobs, and now are very important in Romanian institutional/legislation too. A perspective of employment problems, measures/strategy and actual legislation in Romania is presented in the final part of the article.